Phenotypes of irritable bowel syndrome and strategies for patient-oriented curation of patient - O. V. Gaus; M. A. Livzan (Лечащий Врач)
Objective. To propose a patient-oriented approach to the management of a patient with irritable bowel syndrome based on the identified phenotypes of the disease.Materials and methods. Based on a comprehensive analysis of the interaction of genetic and epigenetic factors, the characteristics of the phenotypes of irritable bowel syndrome have been identified and presented. For each phenotype, individualized treatment regimens for the disease have been developed and tested. To evaluate the effectiveness of the proposed patient-oriented approaches, an open cohort, prospective, randomized study in parallel groups was conducted.Results. With post-infectious irritable bowel syndrome, patients are recommended to prescribe a strain of Lactobacillus paracasei CNCMI1572, as well as correction of eating habits with restriction of salt and products containing lactose. With the phenotype of irritable bowel syndrome with overweight and obesity, patients were offered the restriction of foods with a high glycemic index, the additional appointment of ademetionine, as well as a synbiotic containing inulin, strains of Bifidobacteriumlactis Bl-04, Lactobacillusacidophilus La-14, Lactobacillusrhamnosus Lr-32 and B vitamins In the comorbid phenotype, it is advisable to prescribe the cytoprotector rebamipide. Additionally, a correction of the diet is necessary with the exclusion of trigger foods. With the essential phenotype, patients are recommended to take the probiotic strain Bifidobacterium longum 35624. The use of the proposed patient-oriented strategies in addition to standard therapy made it possible to achieve more effective relief of clinical manifestations and reduce the severity of irritable bowel syndrome, improve mental well-being, and reduce the frequency of relapses of the disease.Conclusion. The proposed patient-oriented approaches to the management of a patient with irritable bowel syndrome based on the identified disease phenotypes can be considered as one of the possible ways to improve the effectiveness of disease therapy.